Mechanical stiffness of TMJ condylar cartilage increases after artificial aging by ribose. (March 2018) - Mirahmadi, Fereshteh; Koolstra, Jan Harm; Lobbezoo, Frank; van Lenthe, G.Harry; Ghazanfari, Samaneh; Snabel, Jessica; Stoop, Reinout; Everts, Vincent
Highlights: Aging-like collagen crosslinking was induced in porcine TMJ with ribose. Mandibular condyle incubated in ribose yielded 50-fold increase in crosslink level. Compressive modulus increases about 1.5 fold after incubation with 0.5 M ribose. Similar biomechanical changes were found throughout the condyle after crosslinking. Abstract: Objective: Aging is accompanied by a series of changes in mature tissues that influence their properties and functions. Collagen, as one of the main extracellular components of cartilage, becomes highly crosslinked during aging. In this study, the aim was to examine whether a correlation exists between collagen crosslinking induced by artificial aging and mechanical properties of the temporomandibular joint (TMJ) condyle. To evaluate this hypothesis, collagen crosslinks were induced using ribose incubation. Methods: Porcine TMJ condyles were incubated for 7 days with different concentrations of ribose. The compressive modulus and stiffness ratio (incubated versus control) was determined after loading. Glycosaminoglycan and collagen content, and the number of crosslinks were analyzed. Tissue structure was visualized by microscopy using different staining methods. Results: Concomitant with an increasing concentration of ribose, an increase of collagen crosslinks was found. The number of crosslinks increased almost 50 fold after incubation with the highest concentration of ribose. Simultaneously, the stiffness ratio of the samples showed a significant increase after incubation with the ribose. Pearson correlation analyses showed a significant positive correlation between the overall stiffness ratio and the crosslink level; the higher the number of crosslinks the higher the stiffness. Conclusion: The present model, in which ribose was used to mimic certain aspects of age-related changes, can be employed as an in vitro model to study age-related mechanical changes in the TMJ condyle.